The size-rank relationship for market shares of consumer packaged goods. Issue 54 (19th November 2020) - Bae, Young Han; Gruca, Thomas S.; Lim, Hyunwoo; Russell, Gary J.
ABSTRACT: This study examines the relationship between market share and its rank for a comprehensive set of product categories and subcategories in the U.S consumer packaged goods industry. Based on prior research, we expect that the slope of the market share-rank relationship will be more consistent with the Zipf distribution at the higher levels of aggregation (category-level versus subcategory-level shares). Two alternative model formulations were examined: the size-rank power law and an exponential alternative used in prior research. Model parameters were estimated across categories (and subcategories) using random coefficients for both the slopes and intercepts. The overall slopes for both samples were significantly higher than −1, the slope consistent with the Zipf distribution. However, as expected, we also found that the slope associated with data from the higher level of aggregation (category level) is flatter than that from the lower level of aggregation (subcategory level). We discuss implications of these results for future research on the size-rank relationship.